Нові досягнення в асиметричній функціоналізації N-(трет-бутилсульфініл)поліфтороалкілімінів - Cherednichenko, Alona S.; Rassukana, Yuliya V. (National University of Pharmacy, 2025)
The review covers the latest achievements in the application of N-(tert-butylsulfinyl)polyfluoroalkyl imines in the asymmetric synthesis and summarizes stereochemical observations of their behavior in different types of reactions (reduction of the C=N bond, addition reactions with organometallic reagents, C-H acids, etc.). Fluorinated N-(tert-butylsulfinyl) imines are convenient substrates for obtaining enantiomerically enriched derivatives of polyfluoroalkyl amines, amino alcohols, amino acids, and heterocyclic systems. In recent decades, various approaches to their functionalization have been proposed. With this in mind, important aspects of their reactivity, regio- and stereochemistry have been systematized in this paper.